THE EXCESSIVE USE OF SOCIAL MEDIA AND ITS RELATIONSHIP TO INSOMNIA AMONG NURSING STUDENTS - deboorah Siregar; Adellia Adellia; Alserina Hideni Harefa; Yonavia Oriza; Deborah Siregar; Elissa Hutasoit (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Social media is online media used to interact and exchange information with other people. Excessive use of social media can negatively impact, one of which can make a person's sleep patterns change, causing insomnia. Insomnia is a condition characterized by a disturbance in the amount, quality, or time of an individual's sleep. This study aimed to analyze the relationship between the excessive use of social media and insomnia among nursing students. This research method was correlational quantitative with a cross-sectional design. The sampling technique used was purposive sampling with a sample size of 207 participants. Data analysis used the chi-square test.The results showed 102 participants (49.3%) actively used social media, and 105 participants (50.7%) were not actively using social media, 103 participants (49.8%) experienced insomnia, and 104 participants (50.2%) do not experience insomnia. This study demonstrated a significant relationship between the excessive use of social media and insomnia among nursing students(p-value 0.01).Therefore, this research can provide information to students to optimize the use of social media to support the learning process and improve students’ sleep quality.